PRODUKSI COOKIES BLONDO SEBAGAI MAKANAN KONSUMSI TAMBAHAN DALAM UPAYA PENCEGAHAN STUNTING DI DESA TENIGA - Yadnya, Made Sutha; Amilia , Serlyana; Irawan , Aditia; Putra, Doddy Setya Darsanti; Jannah, Miftahul; Shahab, Seha; Noviana , Ena; Sukmawati, Sukmawati; Fiandra, Naufal Nanda; Nujulia, Nilti Haeratun; Solihati, Solihati (Jurnal Wicara, 2024)
Teniga Village is one of the villages with coconut plantation potential in North Lombok Regency. Currently, Teniga village itself is faced with the problem of stunting. Responding to the challenge of stunting, which is a significant health problem in Teniga Village, the KKN-PMD team from Mataram University conducted an innovation project to utilize "blondo" to make anti-stunting cakes. Blondo is the residue or dregs of coconut oil (Lombok people usually call it tai lale) which is rich in essential nutrients such as protein, vitamins, and minerals, making it one of the suitable ingredients to prevent stunting. This innovation aims to increase public awareness about the nutritional benefits of blondo and encourage its use as a daily snack to improve children's nutrition. The work program includes nutrition education to local communities, as well as distribution of cookies and educational leaflets. It demonstrates how local resources can be effectively utilized to address public health challenges, and encourages sustainable solutions within village communities